Microbiota Promotes Chronic Pulmonary Inflammation by Enhancing IL-17A and Autoantibodies - Yadava, Koshika; Pattaroni, Céline; Sichelstiel, Anke K.; Trompette, Aurélien; Gollwitzer, Eva S.; Salami, Olawale; von Garnier, Christophe; Nicod, Laurent P.; Marsland, Benjamin J. (American journal of respiratory and critical care medicine, 2016)
Changes in the pulmonary microbiota are associated with progressive respiratory diseases including chronic obstructive pulmonary disease (COPD). Whether there is a causal relationship between these changes and disease progression remains unknown. To investigate the link between an altered microbiota and disease, we used a murine model of chronic lung inflammation that is characterized by key pathological features found in COPD and compared responses in specific pathogen-free (SPF) mice and mice depleted of microbiota by antibiotic treatment or devoid of a microbiota (axenic). Mice were challenged with LPS/elastase intranasally over 4 weeks, resulting in a chronically inflamed and damaged lung. The ensuing cellular infiltration, histological damage, and decline in lung function were quantified. Similar to human disease, the composition of the pulmonary microbiota was altered in diseased animals. We found that the microbiota richness and diversity were decreased in LPS/elastase-treated mice, with an increased representation of the genera Pseudomonas and Lactobacillus and a reduction in Prevotella. Moreover, the microbiota was implicated in disease development as mice depleted, or devoid, of microbiota exhibited an improvement in lung function, reduced inflammation, and lymphoid neogenesis. The absence of microbial cues markedly decreased the production of IL-17A, whereas intranasal transfer of fluid enriched with the pulmonary microbiota isolated from diseased mice enhanced IL-17A production in the lungs of antibiotic-treated or axenic recipients. Finally, in mice harboring a microbiota, neutralizing IL-17A dampened inflammation and restored lung function. Collectively, our data indicate that host-microbial cross-talk promotes inflammation and could underlie the chronicity of inflammatory lung diseases.